Geological belts, plate boundaries, and mineral deposits in Myanmar - Mitchell, A. H. G. (Amsterdam Elsevier, 2018)
Geological Belts, Plate Boundaries and Mineral Deposits in Myanmar arms readers with a comprehensive overview of the geography, geology, mineral potential and tectonic plate activity of Myanmar. The book focuses on the nature and history of the structural belts and terranes of Myanmar, with particular emphasis on the mineral deposits and their relationship to stratigraphy and structure. The country has a long history of plate tectonic activity, and the most recent plate movements relate to the northward movement of the India plate as it collides with Asia. Both of these are responsible for the earthquakes which frequently occur, making the country a geologically dynamic region. Additionally, Myanmar is rich in mineral and petroleum potential and the site of some of Southeast Asia’s largest faults. However, many geoscientists are only recently becoming familiar with Myanmar due to previous political issues. Some of these barriers have been removed and there is emerging international interest in the geology and mineral deposits of Myanmar. This book collates this essential information in one complete resource. Geological Belts, Plate Boundaries and Mineral Deposits in Myanmar is an essential reference for economic geologists, mineralogists, petroleum geologists, and seismologists, as well as geoscience instructors and students taking related coursework.--Provided by publisher.
Introduction -- Myanmar east of the Sagaing Fault. The Shan Plateau west of the Salween -- Myanmar east of the Salween : the Sibumasu-Mong Yawng arc collision and related tin mineralization -- The Mergui group and equivalents in the Slate Belt, Phayaungtaung and the Gaoliogong Range (northeastern Myanmar) -- Paung Laung-Mawchi zone -- Granites, minor intrusions, and mineralization in the Slate Belt, Phayaungtaung, and Gaoligong Range -- Mogok metamorphic belt -- Tagaung-Myitkyina Belt and Katha-Gangaw Range -- Myanmar west of the Sagaing Fault. Popa-Loimye magmatic arc -- Central Burma depression and its petroleum occurrences / Michael F. Ridd -- The Indo-Burman ranges and the Arakan coastal lowland -- Exploration history and petroleum geology of offshore Myanmar / Andrew Racey -- Hukawng Basin, the amber mines, and the Orbitolina limestone -- Jade mines-Loimaw uplift -- Kumon Range -- Myanmar east and west of the Sagaing Fault. Chaun Kan gneiss and the India collision zone in northwestern Myanmar -- Popa-Loimye arc, correlations with Tibet, and alluvial diamonds in Myanmar -- Myanmar orogens and Flysch, potential for mineral discoveries, and Shan scarps and jade mines cross sections.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Geology, Structural -- Burma; Plate tectonics -- Burma; Electronic books